Pulmonary vein triggers, focal sources, rotors and atrial cardiomyopathy: implications for the choice of the most effective ablation therapy. (16th March 2016) - Pison, L.; Tilz, R.; Jalife, J.; Haïssaguerre, M.
Abstract: Understanding of the pathophysiological mechanism(s) underlying atrial fibrillation (AF) is the foundation on which current ablation strategies are built. In the vast majority of patients with paroxysmal AF, the ablation procedure should target the pulmonary veins. In patients with nonparoxysmal AF, however, pulmonary vein isolation alone seems to be insufficient to prevent the arrhythmia. Several recent clinical trials have investigated the concept that rotors (re‐entry based on a meandering central core from which spiral waves emanate) might be the mechanism responsible for sustaining AF. Ablation of these localized AF sources is an important step towards substrate‐driven procedures in persistent AF. Hybrid AF ablation procedures, based on the integration of endocardial transcatheter and epicardial off‐pump surgical techniques, have been introduced to overcome their mutual shortcomings. The long‐term results are encouraging, especially in currently challenging settings such as nonparoxysmal AF and failed endocardial catheter ablation procedures. Abstract : Content List – Read more articles from the symposium: Atrial fibrillation ‐ from atrial extrasystoles to atrial cardiomyopathy. What have we learned from basic science and interventional procedures